Enhancing Institutional Reputation and Student Excellence: The Management of Superior Class Programs in Islamic Education - Sada, Heru Juabdin; Anzanni, Aulia Adhitiya; Mustofa, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study explores the management of the superior class program at Madrasah Ibtidaiyah Negeri 1 (MIN 1) West Lampung, focusing on its role in enhancing student achievement and institutional reputation. The program integrates Islamic values with modern educational practices, structured around four key management components: planning, organizing, implementation, and evaluation. Using a qualitative approach, data were collected through interviews, observations, and document reviews, with a triangulation method ensuring reliability. The findings highlight the program's significant achievements in both academic and non-academic domains, including improved Qur'anic memorization, competitive successes, and strengthened community trust. The management framework emphasizes strategic planning aligned with institutional goals, resource allocation, innovative teaching methods, and rigorous evaluation involving parents and supervisors. The study concludes that the superior class program effectively enhances the institution’s image while providing a holistic education that nurtures students’ cognitive, spiritual, and social development. This study contributes to the discourse on Islamic education by demonstrating the potential of integrating traditional values with modern management practices. The insights gained offer a model for other institutions to adopt similar initiatives, ensuring their relevance and competitiveness in a contemporary educational landscape.